Binge eating disorder: An emerging challenge in public health: Trastorno por atracón: Un desafío emergente en la salud pública - Arauco-Lozada, Tania (2024)
Binge eating disorder (BED) is one of the most common forms of eating disorders. TA is characterized by a pattern of disturbed eating behavior, in which the individual experiences recurrent episodes of binge eating.